Divorce Mediation and Psychological Recovery of Spouses: An Islamic Family Law Analysis and the Importance of Emotional Education in Family Life - Muhammad Masykur Masykur; Sumarjoko kusumo; Rhindra Puspitasari puspita sari; Rokhmat Rizal (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study aims to analyze the psychological conditions of spouses following divorce mediation at the Religious Court of Temanggung and to examine the urgency of emotional education within the family from the perspective of Islamic family law. The study employed a qualitative empirical approach, with data collected through interviews, observations, and documentation and analyzed descriptively. The findings indicate that divorce mediation has been implemented in accordance with applicable legal procedures but has not fully achieved reconciliation due to the high emotional conflict experienced by the parties. Post-mediation psychological impacts include stress, anxiety, and feelings of loss, while social support contributes significantly to psychological adjustment and recovery. From the perspective of Islamic family law, mediation serves not only as a dispute-resolution mechanism but also as an instrument for preserving family welfare. Therefore, emotional education within the family is essential for strengthening communication skills, emotional management, and constructive conflict resolution. This study recommends the development of a psychology-based mediation model integrated with family emotional education.